REVIEW PAPERPulmonary-renal syndrome in patients with systemic connective tissue diseases - Majdan, Maria; Dudek, Anna (Reumatologia/Rheumatology, 2006)
Pulmonary-renal syndrome (PRS) can originate from several connective tissue diseases. It belongs to the potentially life-threatening conditions. Clinically PRS is a combination of diffuse pulmonary hemorrhage and renal involvement including glomerulonephritis, nephrotic syndrome or acute renal failure. Over two-thirds of cases of PRS is caused by various forms of primary systemic vasculitides associated with serum positivity for antineutrofil cytoplasmatic antibodies (ANCA) like Wegener´s granulomatosis, microscopic polyangiitis, pauci-immune necrotizing and crescentic glomerulonephritis, Churg-Strauss syndrome. Goodpasteure’s syndrome accounts for approximately 20% cases of PRS. PRS can be also caused by systemic lupus erythematosus, systemic sclerosis, antiphospholipid syndrome, mixed connective tissue disease, rheumatoid arthritis or Henoch-Schönlein purpura. Until recently diffuse pulmonary hemorrhage connected with rapid progressive glomerulonephritis usually resulted in a bad prognosis. However now, rapid diagnostic process (antibodies identification, kidney and pulmonary biopsy) can speed up a difficult decision of using intense immunosuppressive therapy including cyclophosphamide, pulses of methylprednisolon and plasma exchanges. Simultaneously, the therapy should be supported by artificial ventilation and renal replacement therapy. In some cases such a treatment can be followed by a complete recovery from renal and pulmonary diseases. The combined therapy contributed to considerable reduction in mortality rate that recently has been achieved in PRS patiens.